Editors' Introduction to Regular Research Section - LEE, Jae Kyu (Institutional Knowledge at Singapore Management University, 2007)
The second section of this issue consists of four regular submissions.In “A New Mobile Payment Scheme for Roaming Services”, Ren-Junn Hwang, Sheng-Hua Shiau and Ding-Far Jan present a new mobile payment scheme that supports anonymity while allowing consumers to roam outside of their home operator’s network.Vasudeva Akula and Daniel A. Menascé’s article on “Two-level Workload Characterization of Online Auctions” analyzes the workload of an online auction site. The analysis reveals the presence of heavy tailed distributions and looks at bidding activity during the closing minutes of auctions. The article suggests that results from this analysis could be used to devise dynamic pricing and promotion models to improve revenue throughput of online auction sites.In their article titled “Buyer Agent to Enhance Consumer Awareness: SAATHI”, Sandip Sen, Sabyasachi Saha and Karina Hernandez argue for the need to develop buyer agents that help customers identify products or services that best match their complex preferences. They contrast this type of agents with seller agents developed primarily to push products onto consumers. The authors present SAATHI a prototype of such a buyer agent developed to help its users locate aparments.Our fourth article, “Evolving a ‘Wise’ Integration System for e-Commerce Transactions” by Chima Adiele and Sylvanus A. Ehikioya discusses components of WISE, a system developed to support the integration of content from diverse data sources. The article focuses in particular on the system’s semi-structured data model, its vocabulary of common terms and its integration algorithm.We would like to take this opportunity to thank the reviewers for the detailed feedback they provided to the authors.